2009
DOI: 10.1007/s12562-009-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between surface-reading and cross-section methods using sagittal otolith for age determination of the marbled sole Pseudopleuronectes yokohamae

Abstract: Title:Comparison between surface-reading and cross-section methods using sagittal otolith for age determination of the marbled sole Pseudopleuronectes yokohamae Authors:Jeong-Hoon LEE ABSTRACTTo find an appropriate method for age determination in the marbled solePseudopleuronectes yokohamae in Tokyo Bay, Japan, sagittal otoliths of 1343 individuals were observed by surface-reading and cross-section methods and the results were compared. Opaque zones occurred once a year and were regarded as annuli in both met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
7
1
1
Order By: Relevance
“…Sectioning of otoliths was useful when the whole otoliths were damaged above or below the core, as an age can still be interpreted from the section in those cases. Previous ageing studies performed for a number of species have found that otolith surface readings underestimate age (Blood, 2003;Albert et al, 2009;Lee et al, 2009). Although we did not find any evidence of this in our study, most of our samples were from relatively young fish (,9 years).…”
contrasting
confidence: 66%
“…Sectioning of otoliths was useful when the whole otoliths were damaged above or below the core, as an age can still be interpreted from the section in those cases. Previous ageing studies performed for a number of species have found that otolith surface readings underestimate age (Blood, 2003;Albert et al, 2009;Lee et al, 2009). Although we did not find any evidence of this in our study, most of our samples were from relatively young fish (,9 years).…”
contrasting
confidence: 66%
“…The difference could be attributed to Bortone (1971) estimating ages of D. formosum using whole otoliths while this study sectioned the otoliths before reading. Sectioning otoliths provides more accurate estimates of age in fishes, which have high initial growth early in life, such as the D. formosum , due to the allometric change in otolith growth, which causes the outer increments to be obscured when read whole because of their proximity to each other (Beamish, 1979; Peltonen et al , 2002; Lee et al , 2009). Latitudinal and regional variation in age and growth could also be a factor (Conover & Present, 1990) between the western Atlantic Ocean, where fish for this study were collected and the Gulf of Mexico, where Bortone (1971) collected samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sagittal otoliths from the blind side of the fish were used for age determination and subsequent growth analysis. These otoliths are suitable for reading annuli because the innermost opaque region is located in the center of the otolith [7]. They were immersed in 50% glycerol 6 solution and observed under reflected light against a dark background using a stereomicroscope at 16× magnification (SZX-ILLB100; Olympus Optical Co., Ltd, Tokyo, Japan).…”
Section: Growthmentioning
confidence: 99%
“…They were immersed in 50% glycerol 6 solution and observed under reflected light against a dark background using a stereomicroscope at 16× magnification (SZX-ILLB100; Olympus Optical Co., Ltd, Tokyo, Japan). The number of annuli (opaque zones) on the otoliths was regarded as the age, because previous studies [3,7] have shown that the number of annuli indicate age in marbled sole. The opaque zones are formed only once a year between January and July [7].…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation